2013
DOI: 10.1007/s12031-012-9944-9
|View full text |Cite
|
Sign up to set email alerts
|

PCR-RFLP, Sequencing, and Quantification in Molecular Diagnosis of Spinal Muscular Atrophy: Limits and Advantages

Abstract: Spinal muscular atrophy (SMA) is a severe neuromuscular disease. It is a common cause of infant mortality. Its incidence is estimated at 1 in 10,000. Clinically, age of onset and the symptoms can distinguish four types of SMA. The objective of this study is to make available to clinicians a reliable and reproducible test for the molecular diagnosis of SMA. We evaluate the benefits and limitations of three tests used in our laboratory (RFLP-PCR, sequencing, and qPCR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In our study, the average age of our patients was 9±9 with extremes of 3 months to 32 months. The median was 6.5 months, which is close to the study done in Morocco [6] and that in Chile [7]. On the other hand, the study carried out in Portugal [8] reported that the age of diagnosis was between 0 and 2 years.…”
Section: Epidemiological Aspectssupporting
confidence: 77%
“…In our study, the average age of our patients was 9±9 with extremes of 3 months to 32 months. The median was 6.5 months, which is close to the study done in Morocco [6] and that in Chile [7]. On the other hand, the study carried out in Portugal [8] reported that the age of diagnosis was between 0 and 2 years.…”
Section: Epidemiological Aspectssupporting
confidence: 77%
“…The choice of genotyping method generally depends on individual experiment design. 25,26 Among these included studies, there is no any superiority of these genotyping methods on one another for detecting IL-6 polymorphisms.…”
Section: The Selection Flow and Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Sanger sequencing is considered the gold standard for mutation screening, but is costly and time-consuming for large-scale sequencing. PCR-based methods are only applicable to single diseases, such as spinal muscular atrophy (SMA) and Prader-Willi syndrome 7 8 9 10 11 , leading to a low diagnosis rate. NGS is the newest, most efficient technology for the screening and detection of genetic variation.…”
mentioning
confidence: 99%